2015
DOI: 10.1037/a0038478
|View full text |Cite
|
Sign up to set email alerts
|

Testing the vulnerability and scar models of self-esteem and depressive symptoms from adolescence to middle adulthood and across generations.

Abstract: The vulnerability model states that low self-esteem functions as a predictor for the development of depressive symptoms whereas the scar model assumes that these symptoms leave scars in individuals resulting in lower self-esteem. Both models have received empirical support, however, they have only been tested within individuals and not across generations (i.e., between family members). Thus, we tested the scope of these competing models by (a) investigating whether the effects hold from adolescence to middle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 70 publications
3
49
1
3
Order By: Relevance
“…Due to the one-time measurement of self-esteem, we were not able to test effects of depressive symptoms on self-esteem and how these may have affected the mediators included in our models. Although less consistently and weaker than vulnerability effects, the opposite so-called scar effects have been found in previous research (Shahar and Davidson 2003 ; Sowislo and Orth 2013 ; Steiger et al 2015 ), so we cannot rule out that such effects influenced the reported results. Another consequence of this limitation is that we were not able to test whether the social factors affected self-esteem over time.…”
Section: Discussioncontrasting
confidence: 59%
“…Due to the one-time measurement of self-esteem, we were not able to test effects of depressive symptoms on self-esteem and how these may have affected the mediators included in our models. Although less consistently and weaker than vulnerability effects, the opposite so-called scar effects have been found in previous research (Shahar and Davidson 2003 ; Sowislo and Orth 2013 ; Steiger et al 2015 ), so we cannot rule out that such effects influenced the reported results. Another consequence of this limitation is that we were not able to test whether the social factors affected self-esteem over time.…”
Section: Discussioncontrasting
confidence: 59%
“…Correlations are similar across all of the self-esteem measures, and high self-esteem is positively related to attachment security to parents and romantic partners, narcissistic admiration, narcissism, openness, conscientiousness, agreeableness, extraversion, trait mood, optimism, and life satisfaction; whereas low self-esteem is positively related to narcissistic rivalry, depression, and neuroticism. These patterns are consistent with past research on self-esteem and the Big Five personality traits (Robins, Tracy, Trzesniewski, Potter, & Gosling, 2001), narcissism (Ackerman & Donnellan, 2013), depression (Ulrich Orth, Robins, Widaman, & Conger, 2014;Steiger, Fend, & Allemand, 2015), and optimism (Scheier et al, 1994). Interestingly, the magnitudes of the LSE correlations tend to fall in between those of the existing measures.…”
Section: Correlates Of Self-esteem the Lse Had Evidence Of Criterionsupporting
confidence: 89%
“…Having negative self-regard is highly maladaptive (Beck, 1970;Egan & Perry, 1998;Heimpel et al, 2002;Tsaousis, 2016;Zeigler-Hill, 2011). Low self-esteem in adolescence even has longterm effects on adult mental health decades later (Steiger et al, 2015), and can interact with other dimensions of cognitive processes to influence a wide array of psychosocial adjustment outcomes (Heimpel et al, 2002;Roberts & Monroe, 1999;Southall & Roberts, 2002). Researchers have shown that adolescent selfesteem predicts poorer social constructs in adulthood (e.g., subjective social integration and support; Gruenenfelder -Steiger, Harris, & Fend, 2016).…”
Section: Discussionmentioning
confidence: 99%